Hubungan Efikasi Diri terhadap Kemampuan Perencanaan Karier Peserta Didik Kelas XI MA Cahaya Insani Al Um - Rizki Nur Fitriani; PutriPutri Ria Angelina; Fahmi Irfani (Simpati, 2026)
This study aimed to determine the level of self-efficacy, career planning ability, and the relationship between self-efficacy and career planning ability among eleventh-grade students at MA Cahaya Insani Al Um. A quantitative approach with a correlational research design was employed. The study involved 34 students selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using descriptive statistics and the Pearson Product Moment correlation test. The results indicated that students' self-efficacy was generally at a moderate level (44%), while their career planning ability was also categorized as moderate (38%). The prerequisite tests confirmed that the data were normally distributed and homogeneous. The Pearson correlation analysis yielded a correlation coefficient of r = 0.606 with a significance value of p = 0.000 (p < 0.05), indicating a positive and significant relationship between self-efficacy and career planning ability. These findings suggest that students with higher self-efficacy tend to demonstrate better career planning ability. Therefore, strengthening students' self-efficacy through guidance and counseling services is expected to enhance their readiness in making informed decisions regarding further education and future careers.